El método fonológico en el desarrollo oral en los niños de 4 a 5 años - Ayala Vega, Fernanda Verónica (2022)
In the present work, the phonological method in the oral development of children from 4 to 5 years of age will be announced, since there are a large number of language problems in infants, since most of them affect the articulation of words that are caused by motor difficulties that are involved with speech. The linked project of "Buccophonatory practices for the treatment of dyslalia in children in the first year of Basic Education, with its quantitative-qualitative research approach, which allowed us to verify that a considerable group of infants have certain oral language difficulties presenting alterations in the articulation of phonemes, either by distorting, omitting, substituting or adding the sounds of a word or phrase, therefore it was also observed that the teacher is unaware of dyslalia and articulation errors that children present during language development oral. Therefore, given the detected need, the present proposal arises, which is focused on designing the Bucophonatory Praxis Activities Guide "Little Tongue Jumping" through activities that allow the strengthening of oral development. Finally, the following proposal is a didactic resource that contains bucophonatory praxis activities, the same that directs movements of the tongue, cheeks and facial muscles, which will facilitate the articulation and pronunciation of phonemes. This was validated by experts and users in a satisfactory manner with a significant, creative and innovative contribution, according to the indicated age, since it will allow a favorable development of oral language.